2022
DOI: 10.1001/jamanetworkopen.2022.33730
|View full text |Cite
|
Sign up to set email alerts
|

Association of Influenza Vaccination With SARS-CoV-2 Infection and Associated Hospitalization and Mortality Among Patients Aged 66 Years or Older

Abstract: ImportanceVaccine effectiveness studies have rarely implemented strategies to reduce the healthy vaccinee bias arising from differences in health care–seeking behavior between vaccinated and unvaccinated individuals. Although previous observational studies suggest that influenza vaccination is associated with a reduced risk of SARS-CoV-2–associated outcomes, the healthy vaccinee bias may have led to overestimating the vaccination effect.ObjectiveTo estimate the association between influenza vaccination and SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 44 publications
2
32
1
Order By: Relevance
“…A recent study by Bruxvoort et al showed that recombinant adjuvanted zoster vaccine was associated with a lower risk of COVID-19 diagnosis and lower risk of hospitalization [ 23 ]. Furthermore, Hosseini-Moghaddam et al revealed that among people aged ≥66 years, influenza vaccination was associated with a decreased risk of SARS-CoV-2 infection [ 24 ]. Nevertheless, it remains unclear if these vaccinations induce trained immunity, particularly for COVID-19 protection [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Bruxvoort et al showed that recombinant adjuvanted zoster vaccine was associated with a lower risk of COVID-19 diagnosis and lower risk of hospitalization [ 23 ]. Furthermore, Hosseini-Moghaddam et al revealed that among people aged ≥66 years, influenza vaccination was associated with a decreased risk of SARS-CoV-2 infection [ 24 ]. Nevertheless, it remains unclear if these vaccinations induce trained immunity, particularly for COVID-19 protection [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results support the safety of co-administration of the two vaccines. A population-based cohort study demonstrated that the influenza vaccination was associated with a 22% to 24% lower risk of SARS-CoV-2 infection, a 17% to 32% lower risk of SARS-CoV-2–associated hospitalization, and a 27% to 42% lower risk of SARS-CoV-2–associated mortality during the first 2 years of the COVID-19 pandemic [ 135 ].…”
Section: Influenza Vaccines and Cancer-related Outcomes During Icismentioning
confidence: 99%
“…There is some indication of a cross-variant neutralizing response to the COVID-19 vaccine. The results are mixed, however some studies suggested that influenza vaccination may attenuate the impact of COVID-19 potentially through a vaccine-induced change in innate immunity and a cross-reactivity response [3] , [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%